(untitled) (Acta Scientiarum. Health Sciences, 2017)
This study evaluated the expression of bradykinin (BK) in human placenta from healthy and preeclamptic women. This is a non-randomized experimental study, in which we performed histological analysis of placental tissue to observe changes that occur in each kind of placenta as well as immunohistochemical analysis to investigate the expression of bradykinin. We used ‘Paleontological Statistics software package for education and data analysis’ 3.06 and R for the statistical analysis. The Ethics Committee of the University of Rio Grande do Norte State approved this experiment under protocol number 166370, according to the determinations established by Resolutions 466/12 and 441/11.We found differences between the two kinds of placenta concerning the diameter of the vessels and the rate of cytotrophoblastic invasion. Student’s t-test evidenced significant difference (p = 7.6395 x 10-5) indicating greater marking of BK per section in the healthy placenta group. The result of more significant expression of bradykinin in healthy placenta can be used as a starting point for deeper researches aiming to better characterize and quantify this expression.